Box-Behnken design to optimise 3D printing parameters in applications for fashion products. (30th May 2023) - Spahiu, Tatjana; Kitsakis, Konstantinos; Kechagias, John D.
The fashion industry incorporates innovative technologies to realise new products and designs. Tailored fashion product development very soon tested 3D printing techniques, overcoming many challenging issues. This study investigates the effects of three variables during fused filament fabrication on surface roughness of buttons used for clothing products. First, parameter design is applied to select the experimental area and parameters levels, i.e., the extruding temperature, layer thickness and printing speed are tested following the Box-Behnken experimental design. Then a second-order model is used as a response surface to optimise the parameters and evaluated using contour plots and ANOVA analysis. The values of 230°C extrusion temperature, 0.2 mm layer thickness and 45 mm/s printing speed optimise the average roughness resulting in about three μm for the upper surface.